Diario de un médico desde el centro de aislamiento de la COVID-19 / Diary of a doctor from the isolation center of COVID-19 - Barnés Domínguez, José (Panorama. Cuba y Salud, 2020)
Ante la Pandemia del Nuevo Coronavirus fueron creadas en nuestro país por indicación del Ministerio de Salud Pública las salas de aislamiento para la atención de los pacientes sospechosos y confirmados de la COVID-19. ABSTRACT Due to the Pandemic of the New Coronavirus, isolation rooms were created in our country at the indication of the Ministry of Public Health for the care of suspected and confirmed patients of COVID-19.